2018
DOI: 10.1177/0022034518801537
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Gene Interactions among SPRYs for Nonsyndromic Cleft Lip/Palate

Abstract: contribute to the risk of NSCL/P. For example, Song et al. (2013) identified 3 single-nucleotide polymorphisms (SNPs) (rs2073485, rs2235371, and rs2236909) in IRF6 showing interactions with rs2235373 in PAX9. Liu et al. (2017) reported 9 pairs of SNP-SNP interactions within the region of 16p13.3 potentially important to the susceptibility of NSCL/P. Evidence also supported gene-gene for TGFA-MTHFR and WNT5B-MAFB (Jugessur et al. 2003; Li et al. 2015). However, Beaty et al. (2013) failed to identify any interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…More recently, whole‐exome sequencing (WES) studies have confirmed the role of variants in known NSCLP genes ( IRF6 , CDH1 , CRISPLD2 , FGFR2 , and PAX7) and identified novel candidate genes ( CTNND1 , PLEKHA7 , PLEKHA5 , and ESRP2 ) (Bureau et al, ; Cox et al, ; Pengelly et al, ). Furthermore, there is increasing evidence supporting an additive role for gene–gene interactions in NSCLP, with modifier phenotypic effects (Carlson et al, ; Chiquet et al, ; Li et al, ; D. Liu et al, ; Velazquez‐Aragon et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, whole‐exome sequencing (WES) studies have confirmed the role of variants in known NSCLP genes ( IRF6 , CDH1 , CRISPLD2 , FGFR2 , and PAX7) and identified novel candidate genes ( CTNND1 , PLEKHA7 , PLEKHA5 , and ESRP2 ) (Bureau et al, ; Cox et al, ; Pengelly et al, ). Furthermore, there is increasing evidence supporting an additive role for gene–gene interactions in NSCLP, with modifier phenotypic effects (Carlson et al, ; Chiquet et al, ; Li et al, ; D. Liu et al, ; Velazquez‐Aragon et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 60 ] The older people who live in developed cities are more vulnerable to air pollution than those who live in less developed areas. [ 61 ] Air pollution has adverse effects on respiratory diseases in different Chinese cities, according to research evidence. In Guangzhou, when the temperature is high, the interaction between PM10 and weather has a statistically significant effect on the death rate of respiratory diseases, especially in extreme cold weather.…”
Section: Impact Of Climate Change On Aging Health In Developing Count...mentioning
confidence: 99%
“…Although deleterious changes in these genes can cause cleft in model animals, the contribution of polymorphisms remains to be investigated. And these variants may not play roles independently [16].…”
Section: Introductionmentioning
confidence: 99%